Oro-facial manifestations, oxidative stress marker and antioxidant in serum and saliva of patients with Beta thalassemia major - Abbas Shamsah, Muaid S; Zaidan, Taghreed F (Journal of Baghdad College of Dentistry, 2015)
Background: Beta thalassemia is a typically autosomal recessive form of severe anemia which is caused by an imbalance of two types of protein (alpha and beta) subunits of hemoglobin. Oxidative stress imbalance is the equilibrium between pro-oxidantstatuses in cellular system, which results in damaging the cells. Antioxidant is a chemical that delays the start or slows the rate of lipid oxidation reaction and it play a very important role in the body defense system against reactive oxygen species. The aims of this study were to recorded the oro-facial manifestations in beta thalassemic patients and assess the oxidative stress marker malondialdehyde in serum and salivs and their role in the pathogenesis of beta thalassemia and evaluation the antioxidant uric acid in serum and saliva of those patients. Methods: The study included fifty eight beta thalassemic major patients, twenty eight patients with periodontitis and thirty patients without periodontitis and twenty nine healthy subjects that were age matched with the patients. Oro-facial manifestations recorded clinically, serum and saliva malondialdehyde and uric acid were measured in all subjects. Results : The main oro-facial manifestations were malocclusion ,rodent face, brown pigmentation of oral mucosa and incompetent lip.The mean serum and saliva malondialdehyde was significantly higher in thalassemic patients with periodontitis (p